MicroRNA‐204 Regulates Runx2 Protein Expression and Mesenchymal Progenitor Cell Differentiation - Huang, Jian; Zhao, Lan; Xing, Lianping; Chen, Di (Stem cells (Dayton, Ohio), 2010)
Differentiation of mesenchymal stem cells into a particular lineage is tightly regulated, and malfunction of this regulation could lead to pathological consequences. Patients with osteoporosis have increased adipocyte accumulation, but the mechanisms involved remain to be defined. In this study, we aimed to investigate if microRNAs regulate mesenchymal progenitor cells and bone marrow stromal cell (BMSC) differentiation through modulation of Runx2, a key transcription factor for osteogenesis. We found that miR‐204 and its homolog miR‐211 were expressed in mesenchymal progenitor cell lines and BMSCs and their expression was induced during adipocyte differentiation, whereas Runx2 protein expression was suppressed. Retroviral overexpression of miR‐204 or transfection of miR‐204 oligo decreased Runx2 protein levels and miR‐204 inhibition significantly elevated Runx2 protein levels, suggesting that miR‐204 acts as an endogenous attenuator of Runx2 in mesenchymal progenitor cells and BMSCs. Mutations of putative miR‐204 binding sites upregulated the Runx2 3′‐UTR reporter activity, suggesting that miR‐204/211 bind to Runx2 3′‐UTR. Perturbation of miR‐204 resulted in altered differentiation fate of mesenchymal progenitor cells and BMSCs: osteoblast differentiation was inhibited and adipocyte differentiation was promoted when miR‐204 was overexpressed in these cells, whereasosteogenesis was upregulated and adipocyte formation was impaired when miR‐204 was inhibited. Together, our data demonstrated that miR‐204/211 act as important endogenous negative regulators of Runx2, which inhibit osteogenesis and promote adipogenesis of mesenchymal progenitor cells and BMSCs. STEM CELLS 2010;28:357–364